Introduction to administrative law practice and process : Thursday 23 August, 2001 ... : [papers from a workshop]. - Introduction to Administrative Law Practice and Process, (2001 : Adelaide, (S.A.)); Law Society of South Australia (Adelaide, (S.Aust.) : Law Society of South Australia, Centre for Legal Education, 2001)
Papers from a workshop which aims to introduce participants to the main processes for review of administrative decisions at State and Federal level. Provides practical guidelines to participants in specialised areas of administrative review and develop skills in preparation for and appearing before administrative tribunals.
Workshop 1. Overview of administrative review by courts and tribunals / Chris Finn. -- FOI (State and federal) / Megan Philpot. -- FOI (State and federal) / Martin Stacey. -- Workshop 3. Practice and procedure in administrative appeals tribunals (AAT) / Helen Lacey. -- Practice and procedure in administrative appeals tribunals (AAT) / Casandra Francas. -- Workshop 4. Privacy laws - application and recent developments / Adam Cooper. -- Privacy laws - application and recent developments attachments / Adam Cooper.
Includes bibliographical references.
Keywords: Administrative law -- South Australia